Simulation of mini hydro power based on river configuration at river upstream - Abdul Rahman, Mohamad (2013)
Mini hydro power is a reliable form of energy. Pelton and Turgo turbine are examples of turbine that can be applied to install Mini Hydro Power. The purpose of this paper is to determine the performance and efficiency of Mini Hydro Power at Panching Waterfall, to simulate the flow of upstream river configuration and to determine the suitable turbine to be installed at high head river. Small scale hydro power can be develop in rural areas for clean electrification. The velocity and flow rate of the waterfall is determined and applied to the analysis to identify the suitable turbine to be used. To obtain the results, simulation using ANSYS CFX is done. The solver can determine the output velocity and torque of the flow through the respective cup, and then theoretical results are determined using calculations. The efficiency of Pelton is 0.961 while Pelton Elbow PVC is 0.97. The value of torque is determined from the simulation resuts. The value is-7.9 N.m for Pelton and 19 N.m for Pelton Elbow PVC . The results are then compared with theoretical results which the value for Pelton is 22 N.m and 15.5 N.m for for Pelton Elbow PVC. From these results, the power output is calculated and the values are 9238.7Watt and 9283.3 Watt for Pelton and Pelton Elbow PVC respectively. These results clearly show that Pelton Elbow PVC Turbine is suitable for high head Mini Hydro Power,